2005
DOI: 10.1080/08860220500200395
|View full text |Cite
|
Sign up to set email alerts
|

Silica and Asbestos Exposure in ANCA-Associated Vasculitis with Pulmonary Involvement

Abstract: Silica and asbestos exposure are thought to belong to the triggering factors of antineutrophil cytoplasm antibodies (ANCA)-associated vasculitis. We carried out a study to find out whether patients with pulmonary involvement attributable to ANCA-associated vasculitis (AAV) have been exposed to silicon-containing materials. Thirty-one patients (12 women, 19 men, median age 51 years) were interviewed using a structured questionnaire. Occupational exposure to silicon-containing chemicals was reported by 22.6% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Several case-control studies have shown that among patients with AAV, a high percentage (20 to 45%) were previously exposed to silica [22], [23], [24], [25], [26], [27], [28], [29]. However, these studies have been difficult to interpret; factors such as small numbers of cases and diverse forms of classification for silica exposure contribute to this difficulty, as do the varying strengths of association between AAV and silica that are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several case-control studies have shown that among patients with AAV, a high percentage (20 to 45%) were previously exposed to silica [22], [23], [24], [25], [26], [27], [28], [29]. However, these studies have been difficult to interpret; factors such as small numbers of cases and diverse forms of classification for silica exposure contribute to this difficulty, as do the varying strengths of association between AAV and silica that are reported.…”
Section: Introductionmentioning
confidence: 99%
“…An association with ANCA-associated vasculitis has been described in two studies of asbestos exposures [50, 51] but was not found in at least one study despite an association with silica exposure [52]. Because the interstitial pneumonia that is common in this form of vasculitis can be mistaken for asbestosis, this link may simply be overlooked.…”
Section: Systemic Autoimmune Disease (Said) and Asbestosmentioning
confidence: 99%
“…Few studies have attempted to identify specific targets for asbestos-induced ANA, but one commonality has been the presence of anti-dsDNA in both mice and humans [20, 40, 78], but not rats [41]. Antibodies to neutrophils (ANCA) have been associated with silica and asbestos exposure [51, 79], but the asbestos exposure data came from an occupational exposure questionnaire, so the exposures likely included mixed chrysotile and amphibole. Pfau et al did not find an association with ANCA in their amphibole-exposed cohort [20].…”
Section: Targets Of Autoantibodies and Mechanisms Of Diseasementioning
confidence: 99%
“…Silica is a risk factor for ANCA disease (51,52). ANCA disease can be caused by drugs, including propylthiouracil, hydralazine, D-penicillamine, allopurinol, minocycline and anti-TNF agents (7,8,53).…”
Section: Origin Of the Anca Autoimmune Responsementioning
confidence: 99%